(3JgPjH GdCNdGbs - (3KGHJ Hf SfGf Hf KGHJ Hf bQI GdMQGfj GdUGHF,J (B365 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje QH jSQ , CHhGH gPG GdcJGH SHYI s
(3BNQgG (B:s
(3hjZJfe GdaQUI ai MjGRI ecQeI bO ONQgG Gddg YR hLd deKdg Whd gPg GdOghQ EP SHb ZjQg EdjgG hjchf TQjckG dg ai GdKhGH efMjK dG jfJbU ef KhGHg Ef TGA Gddg JYGdi s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B98s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs